Stoic Caricature in Lucian’s De astrologia: Verisimilitude As Comedy - McNamara, Charles (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2013)
The inclusion of De astrologia in the Lucianic corpus has been disputed for centuries since it appears to defend astrological practices that Lucian elsewhere undercuts. This paper argues for Lucian’s authorship by illustrating its masterful subversion of a captatio benevolentiae and subtle rejection of Stoic astrological practices. The narrator begins the text by blaming phony astrologers and their erroneous predictions for inciting others to “denounce the stars and hate astrology” (ἄστρων τε κατηγοροῦσιν καὶ αὐτὴν ἀστρολογίην μισέουσιν, 2). The narrator assures readers that he, the knowledgeable astrologer, will correct for the “stupidity and laziness” (ἀμαθίῃ καὶ ῥαθυμίῃ, ibid.) that bring about false predictions. The narrator’s credibility quickly decays when he attempts to recast Orpheus, Bellerophon, Icarus, Daedalus, and a host of other mythological figures as Greek astrologers. Lucian’s audience would expect such far-fetched interpretations of myth from the stereo- typical Stoic philosopher, a character lampooned elsewhere in the Lucianic corpus.
Keywords: Lucian; Stoicism